2023
DOI: 10.1111/ijlh.14016
|View full text |Cite
|
Sign up to set email alerts
|

Defining ferritin clinical decision limits to improve diagnosis and treatment of iron deficiency: A modified Delphi study

Abstract: Background Iron deficiency is highly prevalent worldwide and is an issue of health inequity. Despite its high prevalence, uncertainty on the clinical applicability and evidence‐base of iron‐related lab test cut‐offs remains. In particular, current ferritin decision limits for the diagnosis of iron deficiency may not be clinically appropriate nor scientifically grounded. Methods A modified Delphi study was conducted with various clinical experts who manage iron deficiency across Canada. Statements about ferriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…We conducted all analyses from October 2, 2023, to May 29, 2024, using the statistical software R, version 4.3.2 (R Foundation for Statistical Computing). 22 We assessed the association of ferritin cutoff choice with the incidence of iron deficiency diagnoses using the following 3 cutoffs recommended by guidelines and expert panels for the adult general population 4,11,[23][24][25][26][27] : 15, 30, and 45 ng/mL. For each cutoff and patient, we defined an iron deficiency event as the first measurement of ferritin concentrations below that cutoff during the study period and calculated patient-time as the number of days from (and including) inclusion to (and including) the earliest of either an iron deficiency event, if any, or the end of the study period.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted all analyses from October 2, 2023, to May 29, 2024, using the statistical software R, version 4.3.2 (R Foundation for Statistical Computing). 22 We assessed the association of ferritin cutoff choice with the incidence of iron deficiency diagnoses using the following 3 cutoffs recommended by guidelines and expert panels for the adult general population 4,11,[23][24][25][26][27] : 15, 30, and 45 ng/mL. For each cutoff and patient, we defined an iron deficiency event as the first measurement of ferritin concentrations below that cutoff during the study period and calculated patient-time as the number of days from (and including) inclusion to (and including) the earliest of either an iron deficiency event, if any, or the end of the study period.…”
Section: Discussionmentioning
confidence: 99%
“…For the main analysis (definition 1) in this study, ID was defined as SF level <20 mcg/L at both 4 and 6 months CA, as completed as standard practice by the present study hospital’s laboratory. As a secondary analysis (definition 2), ID was defined using SF level <30 mcg/L at both 4 and 6 months CA, as recommended by a recent modified Delphi study for preterm infants ( 16 ). The study was approved by the Research Ethics Board of the IWK Health (Approval 1026862).…”
Section: Methodsmentioning
confidence: 99%
“…Many authors suggested that the diagnostic accuracy of ferritin could be improved by increasing the cutoff to 30 μg/L. 6 , 7 , 8 Such a value has a higher sensitivity (from 85% to 92%) and unchanged specificity (98%), and it is the most accepted threshold used to establish a diagnosis of ID, even in the mildest cases. 9 However, little evidence is available from high‐quality studies to justify specific thresholds.…”
Section: Diagnosismentioning
confidence: 99%
“…The WHO defines ID as serum or plasma ferritin levels <15 ug/L in children older than 5 years, adolescents, and adults and less than 12 ug/L in children younger than 5 years (WHO, 2022). Many authors suggested that the diagnostic accuracy of ferritin could be improved by increasing the cutoff to 30 μg/L 6–8 . Such a value has a higher sensitivity (from 85% to 92%) and unchanged specificity (98%), and it is the most accepted threshold used to establish a diagnosis of ID, even in the mildest cases 9 .…”
Section: Diagnosismentioning
confidence: 99%